Interictal spike quantification in continuous spike-wave of sleep (CSWS): Clinical usefulness of a wearable EEG device - Carvalho, D (2020)
Continuous spike-wave of sleep (CSWS) syndrome is one of the most common epileptic encephalopathies of childhood. Because the associated cognitive/behavioral disturbances relate more to the amount of spike activity than of seizures, methods of spike quantification gained relevance in diagnosis and monitoring treatment. The conventional methodology for quantification of spike index (SI) relies on repeated full 10-20 long-term ambulatory electroencephalography (aEEG), which is both expensive and poorly tolerated.